PENGARUH MOTIVASI ORANG TUA DI MASA PANDEMI TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA KELAS VI DI SDN LENGGAHSARI 01 CABANGBUNGIN BEKASI (Lembaga Pengembangan Kinerja Dosen, 2022)
The success of producing the next generation of competent and reliable people begins with family education. The purpose of this study was to determine the effect of parental motivation on mathematics learning achievement for grade VI students at SD Negeri Lengahsari 01 for the 2019/2020 academic year. The approach in this research is to use the Simple Random technique. After the research data was obtained using a measuring instrument that was compiled, then a quantitative data analysis was carried out. This is done to answer the problem through testing the research hypothesis. Mathematics learning achievement of students is influenced by students' learning motivation. It can be seen from the simple ANOVA calculation that the p-value is smaller than 0.05, thus Ho is rejected, Y or X regression is significant or Learning Motivation has an effect on Mathematics Learning Achievement, with the equation Y = 48.673 + 0.351X, thus the hypothesis research is supported by empirical data. Based on the results of the study, it can be concluded that Mathematics Learning Motivation has an effect on Mathematics Learning Achievement. Thus, if a teacher wants to be successful in carrying out learning activities, he must be able to provide stimulation to students to be interested in participating in the process of learning activities. If students are interested, they will catch and understand easily what the teacher is saying.